Ringtailed Lemur Biology Lemur catta in Madagascar - Jolly, Alison; Sussman, Robert W.; Koyama, Naoki; Rasamimanana, Hanta (Developments in Primatology: Progress and Prospects, 2006)
Ringtailed Lemur Biology is the first comprehensive volume dedicated to the Lemur catta, Madagascar's flagship species, whose black and white tails adorn tourist brochures and children's schoolbooks, and which has been studied in the wild for forty years. Written by leading research scientists in the field, this is the authoritative volume on ringtailed lemur distribution, ecology, social behavior, and health and includes the first maps of their distribution, population, and decline. The editors, and contributors, have united to produce a book of cutting edge knowledge on the lemur species whose troop structure is most like the monkeys of other continents but which proves, like so much else in Madagascar, to be unique.